2020
DOI: 10.1016/j.jpag.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Menarche with Adolescent Health in the Setting of Rapidly Decreasing Age at Menarche

Abstract: Study Objective: This study aimed to investigate the association between age at menarche (AAM) and adverse health indicators in adolescent girls. Design: A retrospective cohort study. Setting: Population-based survey data. Participants: A total of 319,437 female participants aged 12-18 years from the Korea Youth Risk Behaviour Web-based Survey. Interventions and Main Outcome Measures: We assessed associations between AAM (categorized as #10, 11, and $12) and health indicators (poor self-rated health, high psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
1
11
0
3
Order By: Relevance
“…We derived the menarcheal status from the question: ‘Have you begun to menstruate (have periods)?’ with possible answers: ‘No, I haven’t yet’ or ‘Yes, I have at the age of __years and __months’. We applied a recommended cut-off age of 11 years to identify early age at menarche24 25 and tested its sensitivity by replicating the analysis using a later cut-off age of 12 years 25 26…”
Section: Methodsmentioning
confidence: 99%
“…We derived the menarcheal status from the question: ‘Have you begun to menstruate (have periods)?’ with possible answers: ‘No, I haven’t yet’ or ‘Yes, I have at the age of __years and __months’. We applied a recommended cut-off age of 11 years to identify early age at menarche24 25 and tested its sensitivity by replicating the analysis using a later cut-off age of 12 years 25 26…”
Section: Methodsmentioning
confidence: 99%
“…Many Mendelian randomization studies have shown a potential effect of earlier AAM on a broad range of health-related traits [60][61][62][63]. AAM less than 12 years can be considered as an indicator in adolescent health interventions [64]. Given the robust correlation between early AAM and women's health risks, the trend of AAM in the previous study provides an alert to health authorities, and women's health management should be adjusted to respond to the related disease threat.…”
Section: Earlier Age At Menarche and Women's Health Risksmentioning
confidence: 96%
“…We included individual characteristics such as age (categorized as 20s, 30s, 40s and 50s), BMI (< 23, 23–24.99, 25–29.99, and ≥ 30 kg/m 2 ) based on the criteria for Asian populations [ 26 ], occupation (2 groups), current smoking (yes or no), season (Mar-May, Jun-Aug, Sep-Nov, Dec-Feb), and clustering effect of district (‘ gu ’, n = 68) in a generalized estimating equation to adjust for potential confounding effects. We did not include air pollution and regional deprivation index because the analytic model of this study included administrative district of home address, which is also the basis of estimation of exposure to air pollution [ 17 , 27 ], noise [ 28 ], and deprivation index [ 29 ]. In addition, residential proximity to major roadways can be used as a proxy for exposure to traffic-related air pollutants, noise, and other spatial characteristics [ 30 – 32 ].…”
Section: Methodsmentioning
confidence: 99%